Enhancing Islamic Pedagogy and Character Development through Educational Values in Asbab al-Nuzul of the Qur'an - Ridha Aulia; Ilzam Hubby Dzikrillah Alfani; Muhammad Syaiful Anwar; Muhammad Hafidz Khusnadin; Muhammad Fahmi Shihab (MADINAH, 2025)
This study examines the relationship between the concept of asbab al-nuzul in the Qur'an and the educational value contained therein. Asbab al-nuzul, which is the cause of the revelation of the Qur'anic verse, has an important role in understanding the meaning of the verse that is more contextual, as well as providing wisdom that can be applied in the world of education. Therefore, this study aims to explore the educational values that can be taken from asbab al-nuzul and how the strategy of embedding these educational values in the learning process can be used. This research uses a descriptive qualitative method with a literature review as a data collection technique. The results of this study show that the educational values found in asbab al-nuzul include determination, gradual learning, relevance of the context of events to teaching materials, and the formation of disciplined and responsible characters. This study concludes that asbab al-nuzul not only functions as an explanation of the context in which the verse was revealed but also as a means to instill educational values that can be applied in Islamic education, such as increasing faith, creating interesting learning, and developing the character of students. Strategies that can be applied to instill these educational values include relevant opening techniques, counseling, and adjusting the curriculum to the conditions of students.